Tinjauan Zakat, Infak, dan Sedekah dalam Mewujudkan Kemandirian Ekonomi dan Pemberdayaan Mustahik: Zakat, Infaq, and Shadaqa in Achieving Economic Independence and Empowering Mustahik - Subekan, Achmat; Azwar, Azwar (Litera Academica Publishing, 2024)
This study aims to describe the role of zakat, infaq, and shadaqa in achieving economic independence as a form of wealth transfer through the empowerment of mustahik. This research uses a qualitative descriptive approach. The findings show that zakat, infak, and sedekah are wealth distribution instruments in Islam that aim to achieve economic and social balance. These three instruments not only function to reduce economic disparities but also serve as a means to distribute wealth to those in need. Zakat, infaq, and shadaqa help mustahik meet their basic needs while also promoting the creation of economic independence, which is crucial for achieving well-being (falah) according to Islamic perspectives. Economic independence, as referred to in this context, includes the fulfillment of worldly needs and spiritual well-being to attain happiness in the hereafter. This study also emphasizes the importance of economic empowerment of mustahik in breaking the cycle of persistent poverty. By providing skills and capital, mustahik can become self-reliant and improve their quality of life, avoiding dependence that undermines dignity. This approach aligns with Islamic teachings that emphasize the importance of independence and personal dignity, as exemplified by the Prophet Muhammad (peace be upon him).